Digital Business Model Innovation in The Metaverse: Strategic Approaches to Virtual Economy Opportunities - Sharma, Ridhima; Sachdeva, Timcy (LPPM Universitas Duta Bangsa Surakarta, 2024)
The metaverse, an expansive digital ecosystem blending augmented reality (AR), virtual reality (VR), and blockchain technology, is reshaping traditional business models and creating new opportunities in the virtual economy. This paper explores the transformative impact of the metaverse on digital business model innovation. As businesses navigate this emerging frontier, they must adapt to the unique characteristics of the metaverse, including the creation and monetization of virtual goods, immersive customer experiences, and decentralized financial systems. Strategic approaches involve understanding evolving consumer behaviors, ensuring interoperability across various platforms, addressing security and privacy concerns, and navigating ethical and regulatory challenges. The metaverse offers unprecedented potential for innovation, enabling businesses to engage with global audiences in novel ways and create new revenue streams. By examining successful case studies and emerging trends, this analysis provides insights into effective strategies for leveraging the metaverse's potential. As the digital landscape continues to evolve, businesses that embrace these opportunities and address associated challenges will be well-positioned for success in the virtual economy. The metaverse represents a significant shift in how value is created and exchanged, heralding a new era of digital business innovation.